2021
DOI: 10.5114/aic.2021.106894
|View full text |Cite
|
Sign up to set email alerts
|

The influence of acute coronary syndrome on the levels of clopidogrel active metabolite and platelet inhibition in patients with and without CYP2C19 and ABCB1 gene polymorphisms

Abstract: Introduction: Although ticagrelor and prasugrel remain the standard antiplatelet treatments in acute coronary syndrome (ACS), numerous patients still present with indications for clopidogrel use.Aim: We aimed to assess the levels of clopidogrel active metabolite and to evaluate the effect of the drug on platelet inhibition in patients with ACS as compared with those with stable coronary disease. Patients were assessed for the presence of the most common genetic polymorphisms that reduce the absorption (ABCB1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Activated platelets aggregate to form blood clots, leading to AIS ( 20 ). Clopidogrel is commonly used as an antiplatelet agent and its active metabolite can specifically and irreversibly block the binding of ADP to platelet receptors, thereby inhibiting platelet aggregation and reducing the risk of AIS ( 21 ). Although the antiplatelet mechanism of clopidogrel is well established, observational studies have shown that there is considerable variability in response to clopidogrel after antiplatelet treatment, and a suboptimal response may lead to recurrent ischemic events in cardiovascular disease ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets aggregate to form blood clots, leading to AIS ( 20 ). Clopidogrel is commonly used as an antiplatelet agent and its active metabolite can specifically and irreversibly block the binding of ADP to platelet receptors, thereby inhibiting platelet aggregation and reducing the risk of AIS ( 21 ). Although the antiplatelet mechanism of clopidogrel is well established, observational studies have shown that there is considerable variability in response to clopidogrel after antiplatelet treatment, and a suboptimal response may lead to recurrent ischemic events in cardiovascular disease ( 22 ).…”
Section: Discussionmentioning
confidence: 99%